ICSID regulations and rules, in effect on January 1, 1968 - International Centre for Settlement of Investment Disputes ([Washington : ICSID, 1968)
This book discusses the issues involved in foreign investment and international law and how conflicts arising from international investments can be resolved.
usc 26/04/18
Loans
Keywords: Investments, Foreign (International law); Conflict of laws; International Centre for Settlement of Investment Disputes; Arbitration (International law)